Impulse buying behavior in the online context - Öker, Barış. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Online shopping is gaining importance every year all around the world. Many researchers, academicians, and business professionals are trying to get the highest benefit possible from online sales channels. One of the most important phenomena of shopping is impulse buying, which drives a huge amount of sales, hence is paid attention by researchers and professionals for both offline and online contexts. The main objectives of this study are to find out underlying reasons for online impulse buying behavior and understand whether online impulse buying intention changes with respect to online shopping habits as well as demographic characteristics. Theoretical model and statistical hypotheses are formulated based on S-O-R framework. Data collected from 495 online shoppers are analyzed by using descriptive, reliability, correlation, one-way ANOVA, independent samples t-test, and multiple regressions to test hypotheses and provide findings and implications. The results of analyses show that online impulse buying intention is a complicated phenomenon influenced by website and marketing stimuli including visual appeal and security of web store; economic promise, scarcity claim, and social effect by other customers, celebrity, and experts as well as organism-related factors including hedonic motives of shopping, fun seeking, and behavioral drive. The study also shows that hedonic motives, fun seeking, and behavioral drive has significant mediating effects on the relationship between each stimulus and online impulse buying intention. Findings and implications deduced from analyses as well as limitations of the study are provided for researchers, academicians, and professionals at the end of study.
Keywords: Shopping -- Computer network resources.